Patterns of (PSI+) aggregation allow insights into cellular organization of yeast prion aggregates - Tyedmers, Jens (Prion, 2012)
The yeast prion phenomenon is very widespread and mounting evidence suggests that it has an impact on cellular regulatory mechanisms related to phenotypic responses to changing environments. Studying the aggregation patterns of prion amyloids during different stages of the prion life cycle is a first key step to understand major principles of how and where cells generate, organize and turn-over prion aggregates. The induction of the [PSI+] state involves the actin cytoskeleton and quality control compartments such as the Insoluble Protein Deposit (IPOD). An initially unstable transitional induction state can be visualized by overexpression of the prion determinant and displays characteristic large ring- and ribbon-shaped aggregates consisting of poorly fragmented bundles of very long prion fibrils. In the mature prion state, the aggregation pattern is characterized by highly fragmented, shorter prion fibrils that form aggregates, which can be visualized through tagging with fluorescent proteins. The number of aggregates formed varies, ranging from a single large aggregate at the IPOD to multiple smaller ones, depending on several parameters discussed. Aggregate units below the resolution of light microscopy that are detectable by fluorescence correlation spectroscopy are in equilibrium with larger aggregates in this stage and can mediate faithful inheritance of the prion state. Loss of the prion state is often characterized by reduced fragmentation of prion fibrils and fewer, larger aggregates.
Im Titel ist „+“ hochgestellt
Gesehen am 20.09.2018